Effects of Constructivist and Transmission Instructional Models on Mathematics Achievement in Mainland China: A Meta-Analysis - Xie, Chen; Wang, Mingshuai; Hu, Huimin (Frontiers in Psychology, 2018)
This review examined effects of constructivist instructional models and transmission instructional models on mathematics performance in mainland China. Using rigorous inclusion criteria, we identified 89 studies for constructivist instruction and 25 studies for transmission instruction in grades 1-12. Compared with traditional transmission instruction, the weighted mean effect sizes of constructivist instruction and improved transmission instruction were +0.55 and +0.63, respectively. These two effect sizes were not significantly different. Of the included studies, inquiry-based learning, problem-based learning, cooperative learning, autonomous learning, and script-based learning were frequently used constructivist models and grouping teaching and variation teaching were frequently used improved transmission models. All seven models had significant effects on improving mathematics achievement. Our findings implicate that the traditional transmission teaching model needs to be changed in mainland China but the constructivist model is not the only promising approach. The impact of study features on the variation of effect sizes was also discussed.